EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA ROPANG - Novi Kadewi Sumbawati; A Asmini; Heni Juliawati; Binar Dwiyanto Pamungkas (Jurnal Ekonomi & Bisnis, 2020)
This study was conducted with the aim of knowing how the effectiveness of the implementation of the Hope family Program (PKH) in improving the welfare of the Ropang Village community. This study was a descriptive study with data collection methods using observation, interviews, and documentation study. The numbers of samples in this study were 46 samples. The data sources include primary and secondary data. The data analysis technique used was qualitative techniques. Based on the results of research in the field, it was known that the effectiveness of the Hope Familiy Program (PKH) which was measured through four indicators, namely target accuracy, understanding of program objectives, socialization, and program monitoring in Ropang Village had quite effective with a score of 78.80%.